Parenting patterns and socio-economic status with the incidence of stunting in toddlers aged 24-59 months - Ratika, Ratika; Mayangsari, Riska; Supyati, Supyati; Rahmawati, Rahmawati (Arsip Keilmuan Gizi (AKG), 2026)
Stunting is one of the chronic nutritional problems that remains a public health challenge in Indonesia, including in Majene Regency. This study aims to determine the relationship between parenting patterns and socioeconomic status with the incidence of stunting in children aged 24–59 months in Baurung Subdistrict. This research is quantitative with a cross-sectional design. The population of this study was all children aged 24–59 months in Baurung Subdistrict, with a sample of 85 subjects selected using proportional random sampling. Data were collected using questionnaires and analyzed using the Chi-Square test with a significance level of 0.05. The results showed that the prevalence of stunting was 61.2%, while normal nutritional status accounted for 38.8%. There was a significant relationship between parenting patterns and the incidence of stunting (p=0.017). In addition, maternal education (p=0.009), maternal employment (p=0.019), family income (p=0.005), and family expenditure (p=0.005) were significantly associated with stunting. The study concludes that parenting patterns and socioeconomic status are significantly associated with stunting among children aged 24–59 months in Baurung Subdistrict.